A survey of the Ancient North Arabian inscriptions from the Dūmat al-Jandal area (Saudi Arabia) - Norris, Jérôme (Proceedings of the Seminar for Arabian Studies, 2018)
This study aims to present an overview of the Ancient North Arabian (ANA) material from the Dūmat al-Jandal area (modern al-Jawf, north-west Saudi Arabia), taking into account the texts published since the late nineteenth century and those collected during the 2010–2017 seasons of the joint Saudi-Italian-French project at Dūmat al-Jandal (DaJAP). At present, the total number of known inscriptions in that region has reached 812, of which 379 are so far unpublished. Among the latter, there is a small set of texts sharing some characteristics with the three ‘Dumaitic’ inscriptions discovered by Winnett in 1962, which could perhaps support the theory that the inhabitants of Dūmah had indeed developed their own North Arabian script, as did the communities of TaymāΜ and Dadan. A special focus is given to the so-called ‘Mixed Safaitic-Hismaic’ (MSH) inscriptions, which are by far the largest group of ANA texts found around Dūmah, representing approximately 57% of the total corpus. The genres of these mixed texts, their linguistic features, and the connections of their authors with the Nabataeans are the various points raised in the discussion. Some alternative interpretations of previously known inscriptions are suggested in the paper alongside the presentation of new documents, among which is a partial bilingual Nabataean/MSH text dated to AD 125.